Front and Back Matter for Volume 1 Issue 3, November 2024 - Trends in General Medicine and Public Health, Svāsthya (Svāsthya: Trends in General Medicine and Public Health, 2024)
Volume 1, Issue 3, November 2024 This issue consists of 5 articles contributed by 24 authors affiliated with 9 affiliations from three countries, including Indonesia (Sekolah Tinggi Ilmu Kesehatan Medistra Indonesia, Universitas Hindu Indonesia, Indonesian Society of Epidemiologists, Universitas Hang Tuah, Universitas Nusa Cendana, Ende General Hospital), United Kingdom (Royal Society of Tropical Medicine and Hygiene), and Pakistan (Sarhad University of Sciences and Information Technology (SUIT), University of Science and Technology Bannu).